2018
DOI: 10.5935/1518-0557.20180044
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant defense capacity of ovarian tissue after vitrification in a metal closed system

Abstract: ObjectiveThe present study analyzed the quality of bovine ovarian tissue after vitrification in a metal closed chamber, in terms of putative changes in tissue viability (lactate dehydrogenase -LDH- release), anti-oxidant defenses, and redox parameters caused by cryopreservation.MethodsSmall and large fragmented bovine ovarian tissue specimens were vitrified in a metal chamber. After rewarming, tissue samples were fixed or cultured for 48 hours. Glutathione (GSH), protein sulfhydryl content, Total Radical Trapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…There was, however, a drop on stromal integrity after the 48-hour culture of the large tissue fragments. This was an unexpected finding considering that previous studies measuring the rate of tissue necrosis by lactate dehydrogenase levels, did not detect any difference between tissue size and between vitrified and fresh samples after 48 hours in culture ( Massignam et al ., 2018 ). One explanation for the decrease in tissue integrity in large samples in the present study may be that the histology technique used to analyze the samples should be adjusted for larger tissue fragments exposed to a cryopreservation process.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…There was, however, a drop on stromal integrity after the 48-hour culture of the large tissue fragments. This was an unexpected finding considering that previous studies measuring the rate of tissue necrosis by lactate dehydrogenase levels, did not detect any difference between tissue size and between vitrified and fresh samples after 48 hours in culture ( Massignam et al ., 2018 ). One explanation for the decrease in tissue integrity in large samples in the present study may be that the histology technique used to analyze the samples should be adjusted for larger tissue fragments exposed to a cryopreservation process.…”
Section: Discussionmentioning
confidence: 65%
“…Early experiments by Ferreira et al (2010), were performed using the slow freezing procedure and, to our knowledge, there is no similar research on the impacts of tissue sample size on the follicular and stroma integrity after vitrification/rewarming technique. However, it has been shown that the antioxidant defense capacity and tissue viability have similar values for vitrified ovarian tissue cut in small or large fragments, immediately after rewarming and after a 48h culture (Massignam et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, synthetic and plant‐derived antioxidant substances, such as melatonin, resveratrol, and aloe vera extract, have been tested in OT cryopreservation 29,30 . Additionally, vitrification of OT using a metal containment system and found no changes in antioxidant parameters or viability of the rewarmed tissue samples 31 …”
Section: Introductionmentioning
confidence: 99%
“…29,30 Additionally, vitrification of OT using a metal containment system and found no changes in antioxidant parameters or viability of the rewarmed tissue samples. 31 The effectiveness of static magnetic field (SMF) in biological systems has long been proved. 32,33 SMF can penetrate biological tissues and interact directly with mobile charges, such as proteins and ions, as well as magnetic compounds within these systems.…”
mentioning
confidence: 99%
“…The oxidation reduction potential (ORP) is a direct measure of the balance between ROS and antioxidants, and if unbalanced, this can lead to oxidative stress (Agarwal et al., 2016). ROS play a major role in sperm physiology and have been reported to have both, beneficial and harmful effects depending on their concentration and the antioxidant scavenging capacity of the cell, which is diminished by the cryopreservation medium (Liu et al., 2018; Massignam et al., 2018; Taylor et al, 2009). We have previously observed that the addition of EmbryORP ® reduced the ORP of cultured vitrified human embryos.…”
Section: Introductionmentioning
confidence: 99%